Lesões bucais em Pacientes Hospitalizados por COVID-19: Estudo Caso- Controle - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2022)
Patients hospitalized with COVID-19 are susceptible to several complications associatedwith disease severity, including oral changes. The hypotheses suggest that oral manifestations in these patients may be associated with systemic complications of the disease or local viral replication factors. We consider the hypothesis that patients with COVID-19 manifest oral lesions related to the systemic condition. This study aims to investigate the association between oral lesions of hospitalized patients and COVID-19 and analyze whether these may be considered predictors of evolution to death in patients with COVID-19. We carried out a case- control study in which patients were evaluated at Hospital Universitário Regional dos Campos Gerais (HURCG) in Ponta Grossa, PR, Brazil. We included patients with positive RT-PCR test for COVID-19 or patients with influenza symptoms but with negative RT-PCR test (control group). The subjects received an oral physical examination to identify oral lesions with a photographic record collection of salivary content to investigate calcium and salivary phosphatase. Data regarding sociodemographic data and hematological exams were evaluated through electronic medical records. The final sample included 112 patients, with 69 patients testing positive and 43 testing negative for COVID-19. The results showed an association between the presence of oral lesions and hospitalization for COVID-19, and the lesions associated with the disease were "hemorrhagic ulcers", "traumatic ulcers", and "angular cheilitis". We conclude that oral lesions in hospitalized patients are associated with COVID- 19, and these indicate a 13 times greater risk of the individual evolving to death.
Keywords: COVID-19; Manifestações bucais; Equipe hospitalar de Odontologia; Estado Crítico; COVID-19; Oral Manifestations; Dental Staff; Critical Illness; CNPQ::CIENCIAS DA SAUDE::ODONTOLOGIA